Donor and Recipient Outcomes following Robotic-Assisted Laparoscopic Living Donor Nephrectomy: A Systematic Review - Creta, Massimiliano (Biomed Res Int, 2019)
AIMS: We aimed to summarize available lines of evidence about intraoperative and postoperative donor outcomes following robotic-assisted laparoscopic donor nephrectomy (RALDN) as well as outcomes of graft and recipients. METHODS: A systematic review of PubMed/Medline, ISI Web of Knowledge, and Scopus databases was performed in May 2018. The following search terms were combined: nephrectomy, robotic, and living donor. We included full papers that met the following criteria: original research; English language; human studies; enrolling patients undergoing RALDN. RESULTS: Eighteen studies involving 910 patients were included in the final analysis. Mean overall operative and warm ischemia times ranged from 139 to 306 minutes and from 1.5 to 5.8 minutes, respectively. Mean estimated blood loss varied from 30 to 146 mL and the incidence of intraoperative complications ranged from 0% to 6.7%. Conversion rate varied from 0% to 5%. The mean hospital length of stay varied from 1 to 5.8 days and incidence of early postoperative complications varied from 0% to 15.7%. No donor mortality was observed. The incidence of delayed graft function was reported in 7 cases. The one- and 10-year graft loss rates were 1% and 22%, respectively. CONCLUSIONS: Based on preliminary data, RALDN appears as a safe and effective procedure.